2016
DOI: 10.1590/s1413-41522016143529
|View full text |Cite
|
Sign up to set email alerts
|

Dinâmica de protozoários patogênicos e cianobactérias em um reservatório de abastecimento público de água no sudeste do Brasil

Abstract: The current study monitored the water quality of a tropical reservoir (Vargem das Flores) used to supply potable water to seven cities in the metropolitan area of Belo Horizonte, Minas Gerais, southeast Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
2
0
3
Order By: Relevance
“…According to a study of on aquatic parasitosis [38], parasites were still present in river water samples in municipality of Tefé-Amazonas, between October and June because the temperature and humidity conditions were ideal such that they could survive in the external environment. According to [39,40], Brazil is a country in which published studies related to parasites in water are rare, which makes it difficult to ascertain the relative magnitude of parasite contamination.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study of on aquatic parasitosis [38], parasites were still present in river water samples in municipality of Tefé-Amazonas, between October and June because the temperature and humidity conditions were ideal such that they could survive in the external environment. According to [39,40], Brazil is a country in which published studies related to parasites in water are rare, which makes it difficult to ascertain the relative magnitude of parasite contamination.…”
Section: Discussionmentioning
confidence: 99%
“…IMRE et al, 2017) as, according to Hachich et al (2004), lotic environments have a higher incidence of protozoa than lotic aquatic systems. Lopes et al (2017) found maximum concentrations of 0.8 cysts/L and 0.4 oocysts/L in the Vargem das Flores reservoir, a lentic environment intended for supplying Belo Horizonte, Minas Gerais. The lower occurrence of protozoa is associated with removal factors, including sedimentation and inactivation by temperature, ultraviolet radiation (UV) and predation (BROOKES et al, 2004).…”
Section: Resultsmentioning
confidence: 90%
“…Por serem organismos fotossintetizante são dependentes da radiação solar para sobreviver, onde sua densidade varia conforme vários fatores tais como pH, Turbidez, Cor, e da demanda de nutrientes presente no manancial, onde os principais são o Fosforo e o nitrogênio, que geralmente é proveniente de descargas de efluentes provindos de residências e industrias. (Lopes et al, 2016). As variáveis climáticas também exercem grande influência no crescimento do fitoplâncton, como a insolação que tem correlação com o tempo em que o sol está descoberto por nuvens, precipitação na qual contribui para a diluição dos nutrientes (Oliver, 2014;Vieira et al, 2020;Albuquerque et al, 2021) Vários estudos tem mostrado a presença de reservatórios eutróficos no Brasil.…”
Section: Introductionunclassified